Chinese women in the accounting profession. Issue 2 (6th June 2016) - Zhao, Yingqi; Lord, Beverley R.
Abstract : Purpose: This exploratory research aims to investigate the barriers to career advancement for women accountants in China. Design/methodology/approach: Semi-structured interviews were conducted with eight accountants working for business companies and occupying different-level positions. Findings: Women accountants in China encounter barriers throughout their career paths. The main barrier is a negative perception of women's work performance after having a child. Although the modern communist state claims that women have a role equal to that of men in their work contributions, centuries-old Confucian attitudes constrain women in their choices of balance between work and home life. Originality/value: The findings of this research call for enforcement of employment laws in China to give women equal opportunities in both recruitment and promotion. This research contributes to both Western and Chinese existing literature, confirming some prior findings that are contrary to modern China's rhetoric that "Women hold up half the sky". It also adds the perspective of accountants working in business companies rather than public practice accounting firms.